Raoiella of the world (Trombidiformes: Tetranychoidea: Tenuipalpidae) - Beard, Jennifer J.; Ochoa, Ronald; Bauchan, Gary R.; Pooley, Christopher; Dowling, Ashley P.g. (Zootaxa, 2018)
We describe 16 new species and redescribe six established species in the genus Raoiella—R. argenta sp. nov. Beard, R. australica Womersley, R. bauchani sp. nov. Beard & Ochoa, R. calgoa sp. nov. Beard & Ochoa, R. crebra sp. nov. Beard & Ochoa, R. davisi sp. nov. Beard, R. didcota sp. nov. Beard, R. eugeniae (Mohanasundaram), R. goyderi sp. nov. Ochoa & Beard, R. hallingi sp. nov. Beard, R. illyarrie sp. nov. Beard & Ochoa, R. indica Hirst, R. karri sp. nov. Ochoa & Beard, R. macfarlanei Pritchard & Baker, R. marri sp. nov. Beard & Ochoa, R. pandanae Mohanasundaram, R. pooleyi sp. nov. Beard & Ochoa, R. shimpana Meyer, R. tallerack sp. nov. Beard & Ochoa, R. taronga sp. nov. Beard & Ochoa, R. todtiana sp. nov. Beard & Ochoa, R. wandoo sp. nov. Beard & Ochoa. We discuss molecular evidence of species separation, shared character states among groups of species, and patterns in the additions of leg setae throughout ontogeny that occur in the genus. We provide a key to the known species of Raoiella.